The history of Xinjiang - Tian, Weijiang ("Charming Xinjiang" series, 2014)
The History of Xinjiang tells the history of Xinjiang from its prehistorical times, Han Dynasty, Wei, Jin, Sui, Tang, Song, Yuan Dynasties, all the way to Ming and Qing Dynasties, ending in the Republic and People's Republic of China. It discusses different topics like territory, ethnics and the relationship between Xinjiang and China Proper.